EFEKTIVITAS DAKWAH ISLAM MELALUI KOLABORASI SENI KENTONGAN DAN HADROH BANYUMASAN (Studi Komunitas Kenthosh, Rawalo - Banyumas) - Basuni Basuni (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2017)
The purpose of this paper is to study the art of culture Banyumas oriented to the wider community by bringing up simple traditional musical instruments that have value and high quality. The combination of a musical instrument with other musical instruments make a variety of rhythmic harmonization. It is able to make art Kenthongan and Hadroh Bersholawat (Kenthosh) synergize each other. In this modern era the fastest thing faded eroded is a culture. Both culturally in terms of ethics, morals, social relations or art that is summed up in a tradition. Therefore, the reason the author chose the theme of culture as a means of Islamic propaganda is relevant because it is known that religion and culture is one element in the unity of complementary and memeiliki chemistry. Religion without culture is a void, and vice versa. The diversity and characteristic of a region is seen in the surrounding natural and human resources. This is what makes the collaboration between art Kenthongan and Hadroh Bersholawat (Kenthos) popular around the community and broad. Therefore, the author tries to interpret a student’s achievements as well as students in developing the science of lectures that have been in its presence to the surrounding community through kentongan and hadroh bersholawat in Islamic dakwah.